The Behavior of Indonesian Stock Market: Structural Breaks and Nonlinearity - Setianto, Rahmat Heru; Abdul Manap, Turkhan Ali (Gadjah Mada International Journal of Business, 2011)
This study empirically examines the behaviour of Indonesian stock market under the efficient market hypothesis framework by emphasizing on the random walk behaviour and nonlinearity over the period of April 1983 - December 2010. In the first step, the standard linear unit root test, namely the augmented Dickey-Fuller (ADF) test, Phillip-Perron (PP) test and Kwiatkowski-Philllips-Schmidt-Shin (KPSS) test identify the random walk behaviour in the indices. In order to take account the possible breaks in the index series Zivot and Adrews (1992) one break and Lumsdaine and Papell (1997) two breaks unit root test are employed to observe whether the presence of breaks in the data series will prevent the stocks from randomly pricing or vice versa. In the third step, we employ Harvey et al. (2008) test to examine the presence of nonlinear behaviour in Indonesian stock indices. The evidence of nonlinear behaviour in the indices, motivate us to use nonlinear unit root test procedure recently developed by Kapetanios et al. (2003) and Kruse (2010). In general, the results from standard linear unit root test, Zivot and Adrews (ZA) test and Lumsdaine and Papell (LP) test provide evidence that Jakarta Composite Index characterized by a unit root. In addition, structural breaks identified by ZA and LP test are corresponded to the events of financial market liberalization and financial crisis. The nonlinear unit root test procedure fail to rejects the null hypothesis of unit root for all indices, suggesting that Jakarta Composite Index characterized by random walk process supporting the theory of efficient market hypothesis.